Heterogeneous Nitrogen Supply With High Frequency and Ramet Damage Increases the Benefits of Clonal Integration in Invasive Hydrocotyle vulgaris - Kai Sun (Frontiers in Plant Science, 2022)
Nitrogen (N) deposition significantly affects the growth and the function of invasive clonal plants. However, the effects of heterogeneous N supply with different frequencies on the growth and the potential contribution of clonal integration in invasion plants are still unclear, especially in the complex environment considering ramet damage. To address this question, apical and basal ramets of the clonal invader Hydrocotyle vulgaris were connected or disconnected, N was added to the basal ramets with a high frequency, a low frequency, or no supply, and the total N quantity was the same for the different frequency. Furthermore, 8 aphids were placed on the apical ramets, and 30% of each leaf was cut off to cause damage. The connection between ramets significantly increased the biomass, total carbon (C), and total N of the basal and apical ramets. Higher frequency N supply significantly increased the biomass, total C, and total N of the basal ramets and the entire clonal fragment biomass. The damage had no significant effect on the growth of basal and apical ramets. Especially, under the high N frequency and ramet damage condition, the connection between ramets more significantly increased the biomass, total C, and total N of the apical ramets and the entire clonal fragment biomass. In addition, the uptake rates of 15NH4+ and 15NO3- in H. vulgaris had no significant difference, and N supply increased the uptake rates of 15NH4+ and 15NO3- of the basal ramets. Our results suggest that both higher frequency N supply and clonal integration are beneficial to the growth of H. vulgaris. Moreover, the heterogeneous N supply with high frequency and ramet damage increases the benefits of clonal integration in H. vulgaris. These findings improve our understanding of the response of clonal invader H. vulgaris to nitrogen deposition and ramet damage.